2018
DOI: 10.1161/jaha.118.009624
|View full text |Cite
|
Sign up to set email alerts
|

Sapropterin Treatment Prevents Congenital Heart Defects Induced by Pregestational Diabetes Mellitus in Mice

Abstract: Background Tetrahydrobiopterin is a cofactor of endothelial NO synthase ( eNOS ), which is critical to embryonic heart development. We aimed to study the effects of sapropterin (Kuvan), an orally active synthetic form of tetrahydrobiopterin on eNOS uncoupling and congenital heart defects ( CHD s) induced by pregestational diabetes mellitus in mice. Methods and Results Adult female mice were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 54 publications
1
43
0
Order By: Relevance
“…Further, impaired cardiac gene expression and cell proliferation induced by maternal diabetes were normalized with sapropterin treatment. Most strikingly, the incidence of CHDs was lowered from 59% to 27%, and major abnormalities such as AVSD and DORV were absent in the sapropterin-treated group [15]. The study shows a pivotal role of eNOS uncoupling in the pathogenesis of CHDs in diabetic pregnancies (Table 1).…”
Section: Involvement Of Enos Uncoupling and Ros In Pregestational mentioning
confidence: 93%
See 3 more Smart Citations
“…Further, impaired cardiac gene expression and cell proliferation induced by maternal diabetes were normalized with sapropterin treatment. Most strikingly, the incidence of CHDs was lowered from 59% to 27%, and major abnormalities such as AVSD and DORV were absent in the sapropterin-treated group [15]. The study shows a pivotal role of eNOS uncoupling in the pathogenesis of CHDs in diabetic pregnancies (Table 1).…”
Section: Involvement Of Enos Uncoupling and Ros In Pregestational mentioning
confidence: 93%
“…Furthermore, lower NO levels are associated with higher Jarid2 expression and its enhanced interaction with the Notch1 locus, leading to decreased Notch1 expression and a higher incidence of VSDs in offspring of maternal diabetes [14]. Notably, pregestational diabetes lowers fetal BH4 levels, and induces eNOS uncoupling, elevated superoxide generation, as well as altered cardiac gene expression of Gata4 , Gata5 , Nkx2.5 , Tbx5 , and Bmp10 in the fetal heart [15]. Moreover, mRNA levels of GTPCH1 and DHFR, enzymes involved in BH4 synthesis, were also significantly reduced at E12.5 in the fetal heart of offspring from diabetic dams, compared with control [15].…”
Section: Involvement Of Enos Uncoupling and Ros In Pregestational mentioning
confidence: 99%
See 2 more Smart Citations
“…22,23 In mice, the occurrence of fetal malformations in diabetic pregnancy can be reduced by reducing oxidative stress (eg, the antioxidant N-Acetylcysteine) and increasing nitric oxide production (eg, the tetrahydrobiopterin Sapropterin which improves eNOS function). 24,25 However, clinical trials in human pregnancy have shown unexpected adverse outcomes including an increase in the incidence of intrauterine growth restriction. 26 The human trials were not in women with diabetes, and were not powered for uncommon congenital anomalies.…”
Section: Genesmentioning
confidence: 99%